(untitled) (Journal of Namibian Studies : History Politics Culture, 2022)
In this paper, the application of the concept of translanguaging is extended beyond pedagogical and social domains through an analysis of Neshani Andreas’ use of English, Afrikaans and Oshindonga as a unitary linguistic system in The Purple Violet of Oshaantu. The focus is on both novel and author, as translanguaging is the languaging act performed by bilinguals for maximum communicative effect. A multi-competence conceptual framework is utilised alongside translanguaging as a practical theory of language. Textual analysis reveals how Andreas employs translanguaging to affirm her Namibian identity and to highlight the sociocultural practices and realities of rural women in northern Namibia. Andreas demonstrates a use of translanguaging beyond classroom pedagogical practice as an effective creative force and stylistic strategy in fiction. In effect, Andreas appropriates the English language by using her multilingual competence to translanguage. The paper concludes by establishing translanguaging at the vocabulary, sentential, pragmatics and discourse levels.